Influence of leadership empowering behavior on employee innovation behavior: The moderating effect of personal development support - Ye, Pinghao; Liu, Liqiong; Tan, Joseph (Frontiers in Psychology, 2022)
The main purpose of this study is to explore the influence of leadership empowering behaviour (personal development support, participative decision making and delegation of authority) and thriving at work on employee innovation behaviour and analyse the moderating effect of personal development support on participative decision making and innovation behaviour. The questionnaire survey method is used to survey Chinese industrial workers, and a total of 290 valid questionnaires are collected. The model is verified using SmartPLS. Results show that the personal development support and participative decision making dimensions of leadership empowering behaviour have a significant positive influence on employee innovation behaviour. Thriving at work has a significant positive influence on employee innovation behaviour, and personal development support has a significant moderating effect on the relationship between participative decision making and innovative behaviour. This study also finds that participative decision making has a significant positive influence on personal development support and delegation of authority.